2013
DOI: 10.1557/jmr.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Photo-bias instability of metal oxide thin film transistors for advanced active matrix displays

Abstract: Metal oxide optoelectronics is an emerging field that exploits the intriguing properties of the ns orbital-derived isotropic band structure as a replacement for traditional silicon-based electronics in advanced active-matrix information displays. Although the device performance of metal oxide thin film transistors (TFTs) has been substantially improved, the device reliability against external light and gate bias stress remains a critical issue. This paper provides a literature review of light-induced gate bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
158
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 81 publications
2
158
0
Order By: Relevance
“…It is interesting to discuss the role of excessive oxygen species on the bias thermal stress (BTS) instability of the IZO TFTs. Although the effect of oxygen vacancy defect on the BTS-induced V th instability has been intensively investigated with a viewpoint of the experimental and theoretical calculation, the studies regarding excessive oxygen or loosely bonded oxygen are limited [23]. Ide et al [24] reported the bistability of excessive oxygen species on the performance of the IGZO TFTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to discuss the role of excessive oxygen species on the bias thermal stress (BTS) instability of the IZO TFTs. Although the effect of oxygen vacancy defect on the BTS-induced V th instability has been intensively investigated with a viewpoint of the experimental and theoretical calculation, the studies regarding excessive oxygen or loosely bonded oxygen are limited [23]. Ide et al [24] reported the bistability of excessive oxygen species on the performance of the IGZO TFTs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reduction of this excessive oxygen via the metal capping reaction can result in the strengthening of the resistance to external PBS and CCS applications. The natural passivation effect (TiO 2 ) of the back channel region for TC IZO devices cannot be excluded as the origin of their superior electrical stability [23].…”
Section: Resultsmentioning
confidence: 99%
“…4(b). The featured bonding energy peaks A (529.8 eV), B (531.1 eV), and C (531.8 eV) represent the oxygen bonds (Zn-O) without oxygen vacancy, the oxygen bonds with oxygen vacancies, and the oxygen bonds in the hydroxide (OH), respectively [9], [10]. A sufficient annealing time contributes to an enhancement of peak A and reduction of peak B intensities, indicating a reduction of oxygen vacancies or loosely bonded oxygen states, which can act as trapping sites under NBS and NBIS conditions.…”
Section: Methodsmentioning
confidence: 99%
“…IGZO has gained wide popularity and is considered to be the most appropriate candidate (13)(14)(15)(16)(17). IGZO can be easily deposited on large area glass substrates which makes it economical and easily transferrable to the current flat-panel display production facilities.…”
Section: Introductionmentioning
confidence: 99%